Numeracy Literacy in Moodle-Assisted PBL: A Self-Efficacy Perspective - Fathurrohman, Fani Laffanillah; Wardono, Wardono; Susilo, Bambang Eko (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2024)
A person's capacity to make choices and find solutions to issues in life is significantly influenced by their self-efficacy and numeracy literacy level. Using technology in education is one way to try to make it better. One learning approach that uses technology is the Moodle-assisted Problem-based Learning (PBL) model, which blends the PBL paradigm with Moodle-assisted learning. This research aims to: (1) evaluate the impact of a Moodle-assisted problem-based learning model on students' numeracy literacy; and (2) investigate the impact of students' self-efficacy on their mathematical numeracy literacy. This study uses a mixed method approach, with more quantitative data than qualitative data and an explanatory sequential design. The pupils in grade VII at SMPN 5 Cimahi comprise the study's population. A simple random sample method was used to choose the quantitative data. Qualitative data was collected based on the high, medium, and low categories of student self-efficacy. Methods for quantitative data analysis using parametric statistics, including regression, classical completeness, and mean tests. Techniques for analyzing qualitative data include data reduction, presentation, and conclusion drawing. The study's findings demonstrated that (1) Moodle-assisted PBL successfully raised students' literacy in mathematics and numeracy. (2) In Moodle PBL learning, there was a relationship between students' self-efficacy and numeracy literacy